The Internet as a “Public Sphere” - Matačinskaitė, Jurgita (Žurnalistikos tyrimai, 2011)
This paper considers the theory of the Internet becoming part of the “public sphere”. The first part of the paper looks at how the concept of the public sphere was used by different scholars and how they defined the theory of the “public sphere”. The second part of the paper analyses how the theory about the public sphere defined by different scholars works on the practical level.Keywords: internet, network society, newspaper, public sphere, New York Times, virtuality, website.